Relative Importance of Blockchain in Cryptocurrency, Banking & Health Care - Ponnakanti, Hari Priya; Gonen, Bilal (Archives of Business Research, 2020)
This paper looks at the opportunities and challenges of implementing blockchain technology across medical, finance and banking sectors, and provides a clear view which can enable Blockchain for more extents. After going through few articles and papers related to applications of Blockchain, we gained a vivid knowledge on pros and cons on Blockchain applications from each article. Few drawbacks that we encountered are using Power of Work (POW) in medical sector which is destroying the computing ability at a stage when system is getting bigger and eventually which is wasting lots of resources. One study over conceptual proposal on blockchain is the idea of using trade credit as the value of transactions, and this trade credit is in the scope of trade secret which improves trade confidentiality and makes it more secure. Moreover, centralization systems have few risks owing to their dependence on a high scale which could tamper the data or can even block access, change the rules and might even completely shut down the system. Few more drawbacks are designing and building a secure blockchain system is much more difficult on large-scale of banking sector with large database. To address these challenges, recent developments in blockchain technology are enabling novel opportunities in every possible sector by using Trust-worthy cloud, IoT and artificial intelligence, which makes it more powerful and secure. After analyzing Blockchain implementations and identifying their limitations, we conclude with several promising directions for future research.